Diamond deposits : origin, exploration, and history of discovery - Erlich, Edward (Society for Mining, Metallurgy, and Exploration, 2002)
Written for geologists and diamond prospectors, this guidebook provides a general overview of diamond exploration and exploitation. The text covers how to find, recognize, and evaluate the potential of diamond deposits. As examples, the book reviews the history of some important diamond discoveries in the western United States and Russia. Much of the book is focused on geology of common diamond host rocks, including kimberlite and lamproite. In addition, it reviews the occurrence of some unconventional host rocks that have produced some notable diamond discoveries. The material found in diamon.
Keywords: Diamond deposits.; elektronické knihy; electronic books